Study on the influence of automatic voltage control system with dead zone on the stability of hydropower unit. (August 2022) - Xu, Ganggang; Yang, Hongwei; Fan, Guowei
Abstract: The existing research on automatic voltage control of hydropower station is mostly simplified as linear control model, ignoring the dead time and delay effect. Based on the existing automatic voltage control model, this paper considers the dead zone of automatic voltage control, establishes the corresponding theoretical equivalent model of dead zone, and analyzes the influence of dead zone on the stability of hydropower grid connection. In this method, the dead zone is simplified as a smooth nonlinear function, which makes the small signal analysis method suitable for the nonlinear system with dead zone. This method has good guidance for the actual operation. The effectiveness of the method is verified by the analysis of an actual hydropower plant.